Developmental trajectories of anxious and depressive problems during the transition from childhood to adolescence: Personality × Parenting interactions. (10th June 2014) - Prinzie, Peter; van Harten, Leanthe V.; Deković, Maja; van den Akker, Alithe L.; Shiner, Rebecca L.
Abstract: This study examined separate developmental trajectories of anxious and depressive symptoms from childhood to adolescence (9–15 years) in a community-based sample ( N = 290). At three measurement points, mothers and fathers reported on their children's anxious and depressive symptoms, and at Time 1 they reported on lower order child personality facets and on their parenting. By means of growth mixture modeling, three developmental trajectories were identified for anxious symptoms: steady low (82%), moderate increasing–decreasing (5.9%), and high declining groups (12.1%). For depressive symptoms, two developmental trajectories were found: steady low (94.1%) and moderate increasing groups (5.9%). Higher shyness, irritability, and altruism predicted membership in more problematic anxious and depressive groups. The personality facets energy, optimism, compliance, and anxiety were unique predictors for class membership for anxious symptoms, and the effects of shyness, irritability, and compliance were moderated by overreactive parenting. Shyness and irritability increased the probability of following the moderate increasing–decreasing anxiety trajectory, but only in the context of high or average levels of overreactive parenting. Compliance increased the probability of following the moderate increasing–decreasing and high decreasing trajectories in the context of high overreactive parenting. Our results indicate that childhood personality facets differentiate trajectories of anxious and depressive symptoms in theoretically compelling ways.